Hemin activation abrogates Mycoplasma hyorhinis replication in chronically infected prostate cancer cells via heme oxygenase‐1 induction. Issue 10 (9th September 2021) - Huang, Hanxia; Dabrazhynetskaya, Alena; Pluznik, Jacob; Zheng, Jiwen; Wu, Yong; Chizhikov, Vladimir; Buehler, Paul W.; Yamada, Kenneth M.; Dhawan, Subhash
Abstract : Mycoplasma hyorhinis ( M. hyorhinis ) lacks a cell wall and resists multiple antibiotics. We describe here the striking > 90% inhibitory effect of hemin, a natural inducer of the cytoprotective enzyme heme oxygenase‐1 (HO‐1), on M. hyorhinis replication in chronically infected LNCaP prostate cancer cells. The role of HO‐1 in interrupting M. hyorhinis replication was confirmed by HO‐1‐specific siRNA suppression of hemin‐induced HO‐1 protein expression, which increased intracellular M. hyorhinis DNA levels in LNCaP cells. Proteomic analysis and transmission electron microscopy of hemin‐treated cells confirmed the complete absence of M. hyorhinis proteins and intact microorganisms, respectively, strongly supporting these findings. Our study is the first to our knowledge suggesting therapeutic potential for activated HO‐1 in cellular innate responses against mycoplasma infection. Abstract : This study demonstrates inhibition of antibiotic‐resistant mycoplasma M. hyorhinis replication in human prostate cancer cells by the inducible cytoprotective enzyme heme oxygenase‐1 (HO‐1). Hemin induces mRNA and protein for this ubiquitous HO‐1 component of innate cellular immunity. Hemin is the active component of an FDA‐approved drug for another indication and could potentially provide a therapeutic modality for treating mycoplasma infection.